2018
DOI: 10.3892/ol.2018.8840
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting the proliferation and metastasis of hilar cholangiocarcinoma cells by blocking the expression of vascular endothelial growth factor with small interfering RNA

Abstract: The aim of the present study was to investigate whether the proliferation and metastasis of hilar cholangiocarcinoma cells can be suppressed and whether apoptosis can be induced by small interfering RNA (siRNA) repression of vascular endothelial growth factor (VEGF). siRNA sequences targeting the gene were designed and the human hilar cholangiocarcinoma QBC939, HCCC-9810 and RBE cell lines were transfected with VEGF-siRNA plasmids for 48 h. Reverse transcription-quantitative polymerase chain reaction and weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Jiao et al found that 27-Hydroxycholesterol (27HC) induced E(nd)MT in vascular ECs, and the process promoted EMT and migration in breast cancer cells through the alteration of the tumor microenvironment [93]. This was consistent with the studies that VEGF and syndecan-1 in the tumor stroma were significantly upregulated in dysfunctional ECs, simulated angiogenesis, and induced the migration and EMT of epithelial cells [94,95].…”
Section: Epithelial Cell Damage and Repairsupporting
confidence: 60%
“…Jiao et al found that 27-Hydroxycholesterol (27HC) induced E(nd)MT in vascular ECs, and the process promoted EMT and migration in breast cancer cells through the alteration of the tumor microenvironment [93]. This was consistent with the studies that VEGF and syndecan-1 in the tumor stroma were significantly upregulated in dysfunctional ECs, simulated angiogenesis, and induced the migration and EMT of epithelial cells [94,95].…”
Section: Epithelial Cell Damage and Repairsupporting
confidence: 60%
“…Tumors employ several mechanisms to establish a functional vascular system comprised of both blood and lymphatic vessels, to sustain cell growth [ 15 , 16 ]. CCA cells promote neo-vascularization by enhanced expression of angiogenic growth factors, whereas endothelial cells can release inflammatory chemokines to attract leukocytes and establish a pro-fibrotic and pro-angiogenic milieu, which in turn support migration, invasion and EMT [ 17 ]. The paracrine effects between CCA cells and surrounding stromal cells are summarized in Figure 1 .…”
Section: Cca and Cca-associated Tumor Microenvironmentmentioning
confidence: 99%
“…A previous study shown that TEC induces tumor progression and invasion by activating a series of pathways ( 65 ). In addition, TEC can release inflammatory chemokines to attract leukocytes to establish a pro-fibrotic and pro-angiogenic microenvironment and promote migration, invasion, and EMT in CCA ( 66 ). Besides, CCA-associated endothelial cells highly express the erythropoietin receptor, which binds to cell-released erythropoietin in the tumor immune microenvironment, thus promoting proliferation, survival, and invasion of CCA cells ( 67 ).…”
Section: Discussionmentioning
confidence: 99%